The Correlation Between Social Media Usage in Academic Context and Self-Efficacy Towards TPACK of Prospective Science Teachers in Indonesia - Heru Setiawan; Shane Phillipson (Universitas Pendidikan Indonesia, 2020)
The purpose of this study is to investigate the relationship between the frequency of Social Media Usage (SMU) in an academic setting and Self-efficacy beliefs towards TK, TCK, TPK, and TPACK of Indonesian prospective science teachers. This research is quantitative based-research design using a self-administered survey. The research was conducted during the second semester of the academic year 2018/2019 from October to November 2018 in the Faculty of Mathematics and Natural Science of a State University located in Semarang City, Indonesia. The sample consists of 217 Indonesian prospective science teachers from the science and Biology Education Department. The result shows that the average Social Media Usage frequency has a statistically high correlation with TK Self-efficacy, TPK, and TPACK. However, in general, it does not correlate with TCK. Second, Social Media Usage for Download Media (DM), Searching Information (SI), and Entertainment and Motivation (EM) generally have a statistically medium correlation with TK, TPK, and TPACK for both male and female participants. Third, Social Media Usage for professional development (PD) has a medium correlation with TK and high correlation with TPK and TPACK. This study implies that training focuses on the application of social media in teaching, and learning should be integrated to improve Indonesian Prospective Science Teachers' TPACK.